The Influence of Sir Syed Ahmad Khan on Islamic Education in India - Arwan Saputra; Mandra, Mayang Sri; Ellya Roza (Journal of Practice Learning and Educational Development, 2025)
This journal discusses the thoughts of Sir Syed Ahmad Khan, an Indian Muslim reformer, on Islamic education. Islamic education must be able to adapt to modernization and globalization while maintaining basic values. Leading researcher Sir Syed Ahmad Khan was one of the first to emphasize the importance of combining Islamic values ​​with contemporary science. This study explores Sir Syed Ahmad's ideas and contributions to the development of Islamic education in India. The results show that Sir Syed Ahmad's ideas encouraged curriculum renewal, strengthening rationality in Islamic learning, and openness to international cooperation. His theory is relevant as an example of contemporary Islamic education that is contextual, open, and progressive. His thoughts and educational models are important references for Islamic educational institutions in facing the global era.